2011
DOI: 10.3389/fgene.2011.00044
|View full text |Cite
|
Sign up to set email alerts
|

Genome Scan for Parent-of-Origin QTL Effects on Bovine Growth and Carcass Traits

Abstract: Parent-of-origin effects (POE) such as genomic imprinting influence growth and body composition in livestock, rodents, and humans. Here, we report the results of a genome scan to detect quantitative trait loci (QTL) with POE on growth and carcass traits in Angus × Brahman cattle crossbreds. We identified 24 POE–QTL on 15 Bos taurus autosomes (BTAs) of which six were significant at 5% genome-wide (GW) level and 18 at the 5% chromosome-wide (CW) significance level. Six QTL were paternally expressed while 15 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 99 publications
4
41
0
1
Order By: Relevance
“…Another study 8 mapping body weight and growth in a murine intercross found little overlap between known imprinted genes and imprinted QTL (only 2 of 10 loci overlapped confirmed imprinted genes) but all imprinted QTL contained multiple genes predicted to be imprinted by bioinformatic approaches (discussed below in the Identifying molecular signatures of imprinted loci section) 30 . Similar patterns, where most QTL map to regions that do not contain known imprinted genes but do contain bioinformatically predicted imprinted genes, were found in a study of bovine growth and body composition 31 .…”
Section: Imprinting Effects On Complex Traitssupporting
confidence: 65%
“…Another study 8 mapping body weight and growth in a murine intercross found little overlap between known imprinted genes and imprinted QTL (only 2 of 10 loci overlapped confirmed imprinted genes) but all imprinted QTL contained multiple genes predicted to be imprinted by bioinformatic approaches (discussed below in the Identifying molecular signatures of imprinted loci section) 30 . Similar patterns, where most QTL map to regions that do not contain known imprinted genes but do contain bioinformatically predicted imprinted genes, were found in a study of bovine growth and body composition 31 .…”
Section: Imprinting Effects On Complex Traitssupporting
confidence: 65%
“…The MAM is an extracellular domain that mediates protein-protein interactions, and is found in a variety of proteins, of which many are known to function in cell adhesion [96]. The remaining 16 SNPs, which were not described in detail here, accounted for 19.14% of dEBV variation for backfat thickness and, as seen in Table 2, most of them present some fat-related QTL described within their regions [29,65,66,85,97-99], and are of further interest for future investigations on how these SNPs can be influencing backfat thickness deposition in Canchim beef cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there is an increasing body of knowledge on the roles of imprinted genes in livestock production. For example, in a recent genome scan, Imumorin et al (2011) detected quantitative trait loci (QTL) with parent-of-origin effects on growth and carcass traits in the Angus × Brahman cattle crossbred population. A single nucleotide polymorphism (SNP) in IGF2 was found to be associated with an increase in rib eye area and percentage of grade fat (Goodall and Schmutz, 2007).…”
Section: Introductionmentioning
confidence: 99%